Variksenmarjan levinneisyys ja kasvu muuttuvassa arktis-alpiinisessa ympäristössä - Niskanen, Annina (Helsingfors universitet, 2013)
This thesis examines the distribution and growth of nordic crowberry (Empetrum nigrum ssp. hermaphroditum) in relation to climate and local environmental conditions. The aim of the research was to improve the understanding of how environmental variables affect plant distribution and growth. Nordic crowberry has a dominant role in arctic-alpine ecosystems, but detailed study of its responses to environmental variables is lacking. Understanding the drivers and interactions behind nordic crowberry distribution is exceedingly important in a changing environment. Research was carried out on three different spatial scales, allowing for in-depth analysis of the variables and processes affecting nordic crowberry. Climate and field data were modeled with generalized linear models (GLM) and generalized estimating equations (GEE) to demonstrate the effects of the environment on the distribution, coverage, height and reproduction of nordic crowberry. On larger spatial scales the distribution of nordic crowberry can be explained by climatic factors. The species distribution is also affected locally by topography, biotic and abiotic disturbance and prevailing soil conditions. The variation of the factors on different scales reveals complex and often scale dependent causal connections behind the distribution of nordic crowberry. The results are in line with previous nordic crowberry studies and emphasize the importance of scale and response variable selection in biogeographical research. The effects of climate change on vegetation are believed to be most prominent in arctic and alpine areas. The sensitivity or persistence of nordic crowberry is site-specific due to the wide array of climatic and environmental conditions within its range of distribution. The prospects of its future distribution depend on the impacts of environmental change on climate, soil, topography and disturbance. The tolerance, morphology and dominance of nordic crowberry are key factors when considering changes happening in the environment. Tutkielma ...